Recycling of biomass ashes - Insam, Heribert; Knapp, Brigitte A.; SpringerLink (Online service). (Dordrecht New York Springer, 2011)
The use of renewable bioenergy is increasing, and so is the production of associated wastes: biomass ashes. This book presents eleven chapters on the options for recycling such biomass ashes, ranging from their use as fertilizer in agriculture and forestry to their application as a supplement for the production of cement-based materials or bricks. The book also examines the pros and cons for each of the different uses of biomass ashes.
Recycling of Biomass Ashes? Current Technologies and Future Research Needs -- Phosphorus Fertilizing Effects of Biomass Ashes -- Mixtures of Bottom Wood Ash and Meat and Bone Meal as NPK Fertilizer -- Wood Ash Effects on Soil Fauna and Interactions with Carbohydrate Supply: A Mini-Review -- Characterization of Olive Waste Ashes as Fertilizers -- Effects of Ash Applications on Soil Status, Nutrition and Growth of Pinus radiata D. Don Plantations -- Possible Use of Wood Ash and Compost for Improving Acid Tropical Soils -- Ash from Combustion of Cacao Residues for Nutrient Recycling: A Case Study -- The Use of Biomass Combustion Ashes in Brick Making -- Reuse of Woody Biomass Fly Ash in Cement-based Materials: Leaching Tests -- The Swedish Ash Programme with Focus on Bio-ashes. Ashes are a Resource in a Sustainable Society.
Electronic reproduction.
Keywords: Biomass chemicals -- Recycling -- Congresses; Biomass -- Combustion -- Congresses; Biomass -- Recycling -- Congresses; Biomass; Biotechnology; Electronic books